Nachsorge bei gastrointestinalen Tumoren = Follow-up care for gastrointestinal tumors - Ebert, Matthias (Der Onkologe, 2018)
The follow-up care of patients with gastrointestinal cancer is poorly defined. Prospective trials showing that regular follow-up care is advantageous are largely lacking. Follow-up is primarily based on symptom evaluation, as well as on an assessment of nutritional status and the need for psycho-oncological care. Whereas the evidence for regular endoscopic follow-up is well defined in early cancers, the role of follow-up care in advanced cancers is less well defined. This deficit is mainly due to the lack of therapeutic consequences in the case of recurrence. In such cases, cure is only rarely possible, and most studies have failed to demonstrate a survival benefit following standardized follow-up care of these patients. However, in view of the evolving treatment options in recurrent disease and the success of recurrent colorectal cancer treatment, it seems reasonable to define the current status of follow-up care for patients with gastrointestinal cancers.
Gesehen am 11.07.2019